2018
DOI: 10.1186/s13104-018-3692-z
|View full text |Cite
|
Sign up to set email alerts
|

Poor glycemic control impacts heart rate variability in patients with type 2 diabetes mellitus: a cross sectional study

Abstract: ObjectiveWe aimed to determine and compare HRV parameters in poorly and well controlled type 2 diabetes. 54 normotensive type 2 diabetes patients without clinical signs of CAN were enrolled; 29 poorly controlled (HbA1c ≥ 7%) and 25 controls matched for age, sex and BMI. HRV analysis was performed using 24-h ambulatory ECG, with automatic estimation of the time and frequency domain ranges. Comparisons were performed using Mann–Whitney test.ResultsWe included 54 participants (26 males) aged 56 years [43–62], wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 9 publications
1
10
0
Order By: Relevance
“…ere are also 40 subjects (91%) who had hypertension. Since high blood pressure and poor glycemic control is associated with reduced HRV, all hypertensive and diabetic subjects included in our study must be in optimal blood pressure and glycemic control (blood pressure <140/90 mmHg, fasting plasma glucose <130 mg/dL, and post prandial plasma glucose <180 mg/dL, or HbA1C <7.5%) [14,15]. erefore, coronary revascularization may restore autonomic balance, which is characterized by increased heart rate variability towards an optimal level.…”
Section: Discussionmentioning
confidence: 99%
“…ere are also 40 subjects (91%) who had hypertension. Since high blood pressure and poor glycemic control is associated with reduced HRV, all hypertensive and diabetic subjects included in our study must be in optimal blood pressure and glycemic control (blood pressure <140/90 mmHg, fasting plasma glucose <130 mg/dL, and post prandial plasma glucose <180 mg/dL, or HbA1C <7.5%) [14,15]. erefore, coronary revascularization may restore autonomic balance, which is characterized by increased heart rate variability towards an optimal level.…”
Section: Discussionmentioning
confidence: 99%
“…Impairment in glucose homeostasis is associated with lower HRV without diabetes, most prominently in men and individuals with abdominal adiposity 17 . Frequency domain analysis has shown trends towards lower values of sympathovagal balance in poorly controlled patients with T2DM 18 . Reduced HRV is associated with an increased risk of cardiovascular disease and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…[29] Studies have already demonstrated the reduced HRV could be regarded as early indicators of cardiac autonomic dysfunction. [7,30,31] This study found that vitamin D levels of T2DM patients in the deficiency group were associated with reduced SDNN, ASDNN, pNN50, LF, HF, SDANN, and rMSSD. Meanwhile, the LF/HF in the deficiency group was significantly higher than those in the sufficiency group.…”
Section: Discussionmentioning
confidence: 63%